2014
DOI: 10.1016/j.bjhh.2014.03.011
|View full text |Cite|
|
Sign up to set email alerts
|

Are the review criteria for automated complete blood counts of the International Society of Laboratory Hematology suitable for all hematology laboratories?

Abstract: Objectiveto verify whether the review criteria for automated blood counts suggested by the International Consensus Group for Hematology Review of the International Society for Laboratory Hematology are suitable for the Hematology Laboratory of Hospital de Clinicas, Universidade Federal do Paraná.Methodsinitially, the review criteria of the International Society for Laboratory Hematology were adapted due to limitations in the Institution's electronic hospital records and interfacing systems. The adapted review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 14 publications
7
20
2
Order By: Relevance
“…The following can be used for comparison: According to the adapted criteria from the International Society for Laboratory Hematology, the WBC count can range between 4 3 10 3 /ml and 30 3 10 3 /ml (7.5-fold difference) before further analyses in terms of leukopenia or leukocytosis are considered. Neutrophil frequencies can range between 1 3 10 3 /ml and 20 3 10 3 /ml (20-fold difference) (38).…”
Section: Determination Of Optimal Assay Conditionsmentioning
confidence: 99%
“…The following can be used for comparison: According to the adapted criteria from the International Society for Laboratory Hematology, the WBC count can range between 4 3 10 3 /ml and 30 3 10 3 /ml (7.5-fold difference) before further analyses in terms of leukopenia or leukocytosis are considered. Neutrophil frequencies can range between 1 3 10 3 /ml and 20 3 10 3 /ml (20-fold difference) (38).…”
Section: Determination Of Optimal Assay Conditionsmentioning
confidence: 99%
“…This will ensure proper and appropriate treatment and patient care. 17 Our study found that the microscopic examination of peripheral blood smear is gold standard in the diagnosis of various types of anemia. Similarly Farah et al [18] and Lantis et al [19] in their study also found that the automated hematology analyzers were appropriate for screening purposes because it increases the turnaround time and reduces the labor cost.…”
Section: Discussionmentioning
confidence: 85%
“…To discriminate positive samples with the Mindray BC‐6800 analyzer among the initial NRBC‐flagged samples with a subsequent report of an absolute NRBC count >0.02 × 10 9 /L or an NRBC percentage >0.01, a NRBC cutoff of ≥1% was defined as the positive threshold, in accordance with a set of 41 review criteria for automated CBCs developed by the Internal Society of Laboratory Hematology (ISLH) . No false‐negatives were observed at this threshold for either FC or MM (80/80 samples), while a high false‐negative rate (70%, 13/20 samples) was noted for the MM method in samples with NRBCs < 1%.…”
Section: Discussionmentioning
confidence: 99%